Quality of reporting in oncology studies: A systematic analysis of literature reviews and prospects. (April 2017) - Rivoirard, Romain; Bourmaud, Aurélie; Oriol, Mathieu; Tinquaut, Fabien; Méry, Benoîte; Langrand-Escure, Julien; Vallard, Alexis; Fournel, Pierre; Magné, Nicolas; Chauvin, Franck
Highlights: We provide a synthesis about quality of reporting in oncology studies. 2% of included reviews have analyzed quality of reporting of observational studies. Quality of reporting for methodological items is inconsistent in clinical trials. Intrinsic quality of reporting for systematic reviews was satisfactory. Abstract: The present review gives an overview of systematic reviews published in peer reviewed Journals analysing quality of reporting in oncology studies. PUBMED and Cochrane library were searched to identify systematic reviews assessing quality of reporting for randomized controlled trials (RCTs) and observational studies (OBS). Recommendations and primary endpoints used to assess the quality of reporting were described. Intrinsic quality of reporting was analyzed using an Overall Quality Score for literature Reviews (OQSR). Main evaluation themes were overall quality of reporting (20/58) and reporting of Health-Related Quality Of Life (HRQOL) in RCTs (7/58). Reporting recommendations used were not detailed in 56.9% of reviews. Insufficient reporting for the methodological description (randomization, blinding details, and allocation concealment) and the rationale for using specific measure of HRQOL were highlighted. OQSR was significantly higher for reviews published between 2010 and 2014 (after the PRISMA Publication), as compared to those published between 1996–2009 (median OQSR 10 (10–11) versus median OQSR 9 (6–10) respectively, p = 0.0053). Intrinsic quality of reporting is satisfactory and has been improved in the last years.